Skeptical Approach to Religion - More, Paul Elmer (Book collections on Project MUSE., 2015)
This beautifully expressed and carefully developed approach to religious belief, has been called, "an invaluable contribution to the treasury of Christian thought" (Living Church), and "the finest rational approach to religious belief I have ever read." (William Lyon Phelps). Originally published in 1934. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.